Exploration of Ayurveda in the Management of Bilateral Facial Palsy (International Journal of Ayurveda and Pharma Research, 2025)
Facial nerve palsy is the weakness of the facial muscles resulting from damage to the cranial nerve VII (Facial nerve). Unilateral facial palsy is the most common form. Bilateral facial nerve palsy is exceedingly rare and represents 0.3 -2% of all facial palsies. A similar description of the weakness of the face is mentioned in Ayurveda as “Ardita”, a Vata vyadhi. Acharyas included Ardita under 80 Nanatmaja vyadhi of Vata. Ardita management include Navana (nasal administration), Murdhni taila (application of oil on head), Tarpana (nourishing therapy), Nadi sweda, Anupa pisita upanaha (poultice prepared with meat of aquatic animals) and general Vatavyadhi treatments. This report is on a case study of a 36-year-old female patient with bilateral facial nerve palsy for 17 days presented with difficulty in opening mouth, pain behind both ears, difficulty in closure of bilateral eyelids, difficulty in speech for 17 days in the outpatient department of Kayachikitsa, Govt. Ayurveda College, Thiruvananthapuram, Kerala, India. Additionally, she reported pain over both sides of the neck for 14 days. Initial management was done at a hospital near patient’s home, but no significant improvement was noted. She was admitted in our hospital and treated with Ardita line of management initially, gradually attained the recovery from facial palsy in 3 weeks but the neck pain persisted. Then the general line of treatment of Vata vyadhi i.e., Sneha (oleation) Swedas (sudation) were given and got complete recovery from the pain and facial weakness. Assessment was done with ‘House and Breckmann’ assessment scale before and after the treatments. The result showed improvement from grade V to grade I. This case report shows classical Ardita treatment and general Vata vyadhi treatment can be considered in bilateral facial palsy where no serious underlying causes are present.